River sensitivity and sediment connectivity as tools for assessing future geomorphic channel behavior. Issue 3 (2nd July 2020) - Lisenby, Peyton E.; Fryirs, Kirstie A.; Thompson, Chris J.
ABSTRACT : The science of geomorphology is increasingly used to inform river management efforts; however, the complexity of fluvial systems makes predictions of future channel adjustment difficult at best. The geomorphic concepts of landform sensitivity and sediment connectivity are well suited to aid river managers in assessing the probability and variability of river channel responses. This can be especially helpful in planning for impacts of future climate change or changes in management activity. River sensitivity and sediment connectivity datasets provide a necessary reach-in-catchment perspective to inform geomorphic interpretations of river behaviour. Such interpretations constitute a first step towards providing the contextual geomorphic understanding necessary to establish expectations of future channel behaviour. In this paper, we use geomorphic interpretations based on river sensitivity and sediment connectivity datasets to describe the historical trajectory and future adjustment possibilities for four channel reaches in the Lockyer Valley, southeast Queensland (SEQ). We apply our interpretations to three different scenarios of future climate and river management conditions to constrain what forms of geomorphic adjustment are possible for resilient-disconnected, resilient-connected, sensitive-connected, and sensitive-disconnected channels. Using scenario-building exercises to forecast possibilities of river adjustment can aid river managers by establishing expectations of future channel behaviour. This information can then be fed into the decision-making process regarding where to prioritize management actions as part of catchment action planning that works with, not against, the natural behaviour of riverine environments.